Simultaneous Quantification of Ursolic and Oleanolic Acids in Glechoma hederacea and Glechoma hirsuta by UPLC/MS/MS - Grabowska, Karolina; Żmudzki, Paweł; Wróbel-Biedrawa, Dagmara; Podolak, Irma (Planta Medica, 2021)
The content of ursolic acid and oleanolic acid was determined in different plant parts of two Glechoma species, G. hederacea and G. hirsuta. To achieve optimal extraction conditions of ursolic acid and oleanolic acid from plant material, several methods including maceration, heat reflux, Soxhlet, and ultrasonic extraction, as well as various solvents (methanol, dichloromethane, ethyl acetate), were investigated and compared.For the simultaneous quantification of pentacyclic triterpenes in extracts from Glechoma sp., an UPLC-MS/MS was developed and validated. The method exhibited good linearity, precision, and recovery, and it also was simple, specific, and fast. We developed the method for future application in the quality control of plant materials and botanical extracts containing ursolic acid and oleanolic acid. With regard to the triterpene constituents, both G. hederacea and G. hirsuta can be used equally, and the aboveground parts of both species, but the leaves especially, are abundant sources of ursolic acid (7.1 – 7.5 mg/g dry weight [DW]). Dichloromethane as an extractant provided the best extraction efficiency as well as selectivity to obtain Glechoma extracts rich in triterpenes as compared to methanol and ethyl acetate, regardless of the particular extraction technique. Dry dichloromethane extracts from aerial parts of Glechoma sp. obtained by the heat reflux method resulted in products with a high content of UA (17 – 25% w/w) are considered to be convenient and rich sources of this compound.
Keywords: Glechoma hederacea; Glechoma hirsuta; Lamiaceae; ursolic acid; oleanolic acid; quantification; UPLC-MS/MS; optimization